Effect of elevated environmental temperature on the antibody response of mice to Trypanosoma cruzi during the acute phase of infection. - Dimock, K A (1991)
When held at 36 degrees C, Trypanosoma cruzi-infected C3H mice survive an otherwise lethal infection with significantly decreased parasitemia levels and enhanced immune responsiveness. Treatment of T. cruzi-infected mice with the immunosuppressive agent cyclophosphamide indicated that the positive effects of increased environmental temperature were primarily due to enhancement of immunity. A parasite-specific, enzyme-linked immunosorbent assay and immunoblot analysis were used to examine the effect of elevated environmental temperature on the production of anti-T. cruzi antibodies. Both the reactivity and diversity of anti-T. cruzi antibodies were found to be lower in infected mice held at 36 degrees C than in infected mice held at room temperature. However, reactivity and diversity could be enhanced by vaccination with culture forms of the parasite.